Tax Agressiveness: Study on Food And Beverage Company Listed In Indonesia and Thailand - Tahliya, Thiya; Hartinah, Siti (Amkop Management Accounting Review (AMAR), 2025)
This research aims to examine the impact of Inventory Intensity, Profitability, and Firm Size on tax aggressiveness undertaken by the Company. Tax aggressiveness can be carried out both legally (tax avoidance) and illegally (tax evasion) with the aim of minimizing the company's tax burden, which can certainly harm a country. This research employs the panel data regression analysis technique utilizing E-views 12 software. The population in this study focuses on food and beverage corporations registered on the Indonesia Stock Exchange (BEI) and the Stock Exchange of Thailand (SET). The sampling method utilized was purposive sampling, resulting in a final total of 26 corporations on the IDX and 15 corporations on the SET. The test results indicate that Inventory Intensity for BEI companies has no significant impact on tax aggressiveness. Next, Inventory Intensity of SET Companies has a significant negative impact on Tax Aggressiveness. Profitability of BEI and SET Companies has no significant impact on Tax Aggressiveness Practices, whereas the Firm Size of BEI and SET Companies influence Tax Aggressiveness Practices significantly